FLUKTUASI POPULASI Chaetosiphon fragaefolii Cockerell (HEMIPTERA: APHIDIDAE) PADA PERTANIAN STROBERI (Fragaria ananassa Duch.) ORGANIK DAN NON ORGANIK DI KOPENG, SEMARANG - , Ghidion Rajagukguk ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research were to find out the patterns of fluctuations and the factors which regulate the population of Chaetosiphon fragaefolii on organic and non-organic strawberry agriculture. The research was conducted in August until October 2013 in Getasan, Kopeng, Central Java using systematic sampling technique. The research conducted by recording the density of population of C. fragaefolii, abiotic factors and density of natural enemies data every week for 3 months. The data obtained was reconstructed to form graphic fluctuation. The correlation test and multiple linear regression were used to analyze the relationship between population density of C. fragaefolii with abiotic factors and density of natural enemies . The results showed that the role of natural enemies in regulating populations of C. fragaefolii among other things, were Arachnids, Chrysopha esakii, Cheilomenes sexmacullata and Paederus fuscipes. The nonorganic soil population density peaks occurred at seventh week (5,94 individuals/plant) while an organic soil population density peaks occurred at eighth (1,52 individuals/plant), tenth (1,84 individuals/plant) and twelfth week (1,72 individuals/plant). The correlation test and multiple linear regression showed that at non-organic soil, wind speed (r=-0,60) and natural enemies (r=0,86) significantly affect population density C. fragaefolii and the population density was determined by abiotic factors and natural enemies as much as 85% while in the organic soil, temperature (r=0,60), humidity (r=-0,59) and natural enemies (r=0,68) significantly affect population density C. fragaefolii and the population density was determined by abiotic factors and natural enemies as much as 61 %.